Interpersonal Communication and Work Motivation on Teacher Performance at SDI Insan Taqwa South Cikarang - Vivi Bunga Damayanti; Indah Rizki Maulia; Heni Rohaeni (Journal of Social Science, 2024)
This research aims to examine the influence of interpersonal communication and work motivation on teacher performance at SDI Insan Taqwa South Cikarang. The population in this study were all teachers at SDI Insan Taqwa South Cikarang. The method in this research is a quantitative method with a population of all teachers at SDI Insan Taqwa South Cikarang with a sample of 47 respondents. Based on the research results in the Partial Test (T), the Interpersonal Communication Variable (X1) has a significant positive influence on Teacher Performance with t count > t table (5.889 ? 1.67943) with Sig. 0.000 ? 0.05. The Work Motivation variable (X2) has a positive and significant influence on Teacher Performance by obtaining t count > t table (2.811 ? 1.67943) with a Sig value. 0.003 ? 0.05. Furthermore, in the Simultaneous Test (F), the Interpersonal Communication and Work Motivation variables simultaneously have a positive effect on the Teacher Performance variable with a value (f count) of 9,072 > 3.209 (F table) with a value of Sig. 0.001 ? 0.05. Then the Determination Test (R2) showed that 29.2% of teacher performance (Y) was influenced by Interpersonal Communication (X1) and Work Motivation (X2). Meanwhile, the remaining 70.8% was influenced by other variables not examined in this research.